UPAYA MENINGKATKAN PENGETAHUAN DAN KESADARAN MASYARAKAT TENTANG PENTINGNYA RUANG TERBUKA HIJAU DI PERMUKIMAN PADAT - Mohammad Ischak; Muhammad Burhannudinnur (Universitas Trisakti, 2020)
The existence of open space in densely populated settlements in the city of Jakarta has a very important role in its function as controlling the environment, microclimate, sosial community, and economy of the population. Until now, the total area of open space in Jakarta is still below 30% as a requirement mandated by Law number 26 of 2007 due to a number of reasons, one of which is the very dense land used as a residence. in the condition of the lack of available green open space, the people living in dense settlements are not yet fully aware of the importance of the existence and efforts of structuring green open space around their settlements in supporting their daily lives. The community service program aims to increase knowledge as well as public awareness of the importance of green open space within inhabited residential areas. To achieve this goal, a consultation and pilot method for structuring green open space is used, which begins with counseling, discussion, and a pilot on how to organize green open space in densely populated areas in Meruya Selatan Village. The results obtained through the community service program are increased awareness and enthusiasm of the community to organize the open space around the residence they inhabit.